Silver nanoparticles for enhanced dye degradation - Deepak Gola; Anu kriti; Neha Bhatt; Medha Bajpai; Astha Singh; Arvind Arya; Nitin Chauhan; Sunil Kumar Srivastava; Pankaj Kumar Tyagi; Yamini Agrawal (Current Research in Green and Sustainable Chemistry, 2021)
Dye wastewater discharged after improper treatment is very harmful for environment and living creatures. As per mandate, the dye wastewater should be treated well in order to prevent any negative effects after discharge. Although there are various methods which are in use, however most of these methods have some or the other associated disadvantages i.e., high cost, generation of secondary pollutants, low efficiency, complexity etc. The objective of this study is to identify the dye degradation (orange and blue dye-individually/mixture) potential of chemically synthesized silver nanoparticles (CH-AgNPs) along with NaBH4. Literature studies highlighted the efficacy of AgNPs for individual dye degradation, however it is very important to study the degradation potential of nanoparticles in presence of dye mixture (to mimic the natural wastewater condition). In the present study, the rapid synthesis of silver nanoparticles (CH-AgNPs) was obtained by using trisodium citrate solution. The developed CH-AgNPs were examined for UV–vis Spectrophotometry (maxima-422 nm), Zeta Potential (−6.70 ​mV), and Transmission Electron Microscopy (spherical shape with size range of 8–40 ​nm), highlighting the nano-size and stability of synthesized CH-AgNPs. For catalytic activity, CH-AgNPs and NaBH4 were tested for dye degradation potential for Orange and Blue dyes individually and in mixture (orange ​+ ​blue dye). It was observed that with increase in dye concentration from 50 ​ppm to 200 ​ppm, NaBH4 showed 28% and 25% removal for blue and orange dyes, respectively. However, when CH-AgNPs ​+ ​NaBH4 was used, up to 100% degradation was obtained from blue dye, however the degradation of orange dye has shown 97.4% degradation. Further, as the wastewater contains multiple dyes, therefore in dye mixture studies (orange ​+ ​blue dye- 50 ​ppm), 100% degradation was achieved with NaBH4+CH-AgNPs in just 5 ​min, highlighting the efficient catalytic ability of NaBH4+AgNPs. The results clearly highlighted the potential of CH-AgNPs in enhancing the dye degradation of orange and blue dyes-individually and in mixture, therefore the present study is relevant for further research to identify the best dye degradation agents, especially in presence of dyes mixture.